1993
DOI: 10.1115/1.2910095
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Analysis of Rotating Cavitation in Inducers

Abstract: Rotating cavitation was analyzed using an actuator disk method. Quasi-steady pressure performance of the impeller, mass flow gain factor, and cavitation compliance of the cavity were taken into account. Three types of destabilizing modes were predicted: rotating cavitation propagating faster than the rotational speed of the impeller, rotating cavitation propagating in the direction opposite that of the impeller, and rotating stall propagating slower than the rotational speed of the impeller. It was shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(27 citation statements)
references
References 2 publications
2
23
0
Order By: Relevance
“…As observed in the experiments, this value slightly decreases with cavitation parameter. However, the numerical frequencies of that supersynchronous phenomenon remain about 25% larger than experimental values, as already observed in analytical models by Tsujimoto et al 10 and Joussellin and de Bernardi. 11 For a lower cavitation parameter (σ = 0.08), a stable configuration appears (Fig.…”
Section: Four-blade Cascade Computation: Unsteady Behaviormentioning
confidence: 48%
See 1 more Smart Citation
“…As observed in the experiments, this value slightly decreases with cavitation parameter. However, the numerical frequencies of that supersynchronous phenomenon remain about 25% larger than experimental values, as already observed in analytical models by Tsujimoto et al 10 and Joussellin and de Bernardi. 11 For a lower cavitation parameter (σ = 0.08), a stable configuration appears (Fig.…”
Section: Four-blade Cascade Computation: Unsteady Behaviormentioning
confidence: 48%
“…They are based on stability analyses and linear approach and take into account the total flow rate variations through a cavitating blade-to-blade channel, 10,11 or calculate the flow around attached cavities. 12,13 To improve the understanding and the prediction capability of cavitation instabilities, numerical and experimental analyses are carried out in France through collaborations between the Laboratoire des Ecoulements Géophysiques et Industriels, the Rocket Engine Division of SNECMA Moteurs and the French space agency Centre National d'Etudes Spatiales.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been also shown that other forms of flow instabilities, like rotating cavitation, are promoted by particular combinations of the values of the dynamic transfer matrix elements. 2 Under this point of view, the cavitation compliance and, more so, the mass flow gain factor play a crucial role, as clearly shown by a number of analytical and experimental analyses. 6,7 It is therefore apparent that the characterization of the dynamic matrices of cavitating inducers and turbopumps is a necessary step for the prediction and control of the unstable behavior of this kind of machinery.…”
Section: Introductionmentioning
confidence: 95%
“…In the linearized approximation for incipent small-amplitude flow oscillations this issue is traditionally realized by means of the dynamic transfer matrix, which relates the complex amplitudes of the pressure and flow oscillations at the inlet and outlet crosssections of the machine. [1][2][3][4][5] The close connection between the elements of the dynamic matrix of inducers and turbopumps and the occurrence of potentially dangerous flow instabilities has been widely illustrated in the open literature. The pump resistance, as an example, plays a central role in determining the quasi-static unstable behavior of the machine.…”
Section: Introductionmentioning
confidence: 99%
“…Virtually all of the experimental work on the dynamics of pumps has been necessarily conducted in ground-based test facilities (see, for example, [10][11][12]14]), and much attention has therefore focused on the instabilities that are observed in pumping systems in a nonaccelerating environment (for example, [16][17][18][19][20][21]). Among these much-studied instabilities are those caused by cavitation in the pump: for example, rotating cavitation [18][19][20][21] and cavitation surge [16,20].…”
mentioning
confidence: 99%